Determination of Cyanide Content and Heavy Metals (Cu, Ni, Cd, & Pb) in Different Processed Cassava Meal in Abraka Metropolis, Delta State, Nigeria - Udezi, Mercy Eloho (Universitas Sanata Dharma, 2025)
Cassava is a tuberous plant in Nigeria that can be processed into different meal but its various forms contains a trace concentrations of cyanide, cadmium, nickel, lead and copper that are not only essential for man but toxic if their concentration levels are high. This study determined the cyanide content and some heavy metals in different processed cassava meal sold in markets at Abraka and its environs. Samples of fufu, garri, starch, and fresh cassava were collected from five selected markets in Abraka. Cyanide concentration was determined using AOAC (1990) method of alkaline titration steam distillation of the sample using silver nitrate. While copper, cadmium, nickel and lead were determined using the Atomic absorption spectrophotometer. Results for the cyanide levels were 7.56 mg/kg for fresh cassava, 5.4 mg/kg for starch, 3.24 mg/kg for garri, 2.16 mg/kg for fufu. The levels were in the order, fresh casava starch garri fufu. The heavy metals concentration of copper (Cu), were (mg/kg) 2.04 for fresh cassava, 1.62 for garri, 1.44 for fufu, and 1.02 for starch. The levels were in the order, fresh cassava garri fufu starch. The concentration of cadmium (Cd) were (mg/kg) 3.14 for fresh cassava, 1.03 for garri, 1.47 for fufu, 2.84 for starch. The levels were in the order, fresh cassava starch fufu garri. The concentrations of nickel (Ni) were (mg/kg) 2.46 for fresh cassava, 1.89 for garri. 1.94 for fufu and 1.73 for starch. The levels were in the order, fresh cassava fufu garri starch. Lead (Pb) was not detected in all the samples. From the results obtained in this study, fufu is the safest for consumption due to the low contents of cyanide and heavy metals. Garri is also considered to be safe as they fall within the WHO permissible limit for those metals. Hence, proper processing of cassava products should be encouraged to reduce bioaccumulation of cyanides levels in them.